FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELLITUS TIPE II DI PUSKESMAS NAGASWIDAK KECAMATAN SEBERANG ULU II KOTA PALEMBANG TAHUN 2025 - Sri Mulyati; Medy Purwanto; Devi Marlina (Journal of Innovative and Creativity, 2026)
Type II diabetes mellitus (T2DM) poses an increasing global health threat with a rising prevalence associated with modifiable risk factors. This study aimed to identify the association between smoking behavior, physical activity, and body mass index (BMI) with T2DM occurrence at Nagaswidak Public Health Center, Palembang in 2025. A cross-sectional analytic design was employed, involving 110 adults aged over 15 years. Primary data were collected using validated questionnaires for smoking status and physical activity (IPAQ short form), alongside anthropometric measurements for BMI. Secondary data related to diabetes diagnosis were obtained from medical records. Data were analyzed univariately, bivariately with Chi-square tests, and multivariately using logistic regression. The results showed significant associations between smoking, low to moderate physical activity, high BMI, and the incidence of T2DM (p < 0.05). Respondents who smoked or had lower physical activity and abnormal BMI had higher likelihoods of developing T2DM. These findings highlight the critical role of lifestyle factors in diabetes prevention and management. It is recommended that community health programs emphasize smoking cessation, promotion of physical activity, and weight control to reduce T2DM prevalence. Future studies with longitudinal designs are suggested to explore causal inference further.